How do divergent ecological strategies emerge among marine bacterioplankton lineages?. Issue 9 (September 2015) - Luo, Haiwei; Moran, Mary Ann
Highlights: Bacterial specialization in ocean microenvironments is reflected in their genome content. Phylogenomic reconstructions are revealing bacterioplankton evolutionary history. Competing evolutionary models have different implications for bacterial adaptation. Abstract : Heterotrophic bacteria in pelagic marine environments are frequently categorized into two canonical ecological groups: patch-associated and free-living. This framework provides a conceptual basis for understanding bacterial utilization of oceanic organic matter. Some patch-associated bacteria are ecologically linked with eukaryotic phytoplankton, and this observation fits with predicted coincidence of their genome expansion with marine phytoplankton diversification. By contrast, free-living bacteria in today's oceans typically live singly with streamlined metabolic and regulatory functions that allow them to grow in nutrient-poor seawater. Recent analyses of marine Alphaproteobacteria suggest that some free-living bacterioplankton lineages evolved from patch-associated ancestors up to several hundred million years ago. While evolutionary analyses agree with the hypothesis that natural selection has maintained these distinct ecological strategies and genomic traits in present-day populations, they do not rule out a major role for genetic drift in driving ancient ecological switches. These two evolutionary forces may have acted on ocean bacteria at different geological time scales and under different geochemical constraints, with possible implications for future adaptations to a changing ocean. New evolutionary models and genomic data are leading to a more comprehensive understanding of marine bacterioplankton evolutionary history.